Radiation Doses Received by Major Organs at Risk in Children and Young Adolescents Treated for Cancer with External Beam Radiation Therapy: A Large-scale Study from 12 European Countries - Diallo, Ibrahima; Allodji, Rodrigue S.; Veres, Cristina; Bolle, Stéphanie; Llanas, Damien; Ezzouhri, Safaa; Zrafi, Wael; Debiche, Ghazi; Souchard, Vincent; Fauchery, Romain; Haddy, Nadia; Journy, Neige; et al. (International journal of radiation oncology, biology, physics, 2024)
Childhood cancer survivors, in particular those treated with radiation therapy, are at high risk of long-term iatrogenic events. The prediction of risk of such events is mainly based on the knowledge of the radiation dose received to healthy organs and tissues during treatment of childhood cancer diagnosed decades ago. We aimed to set up a standardized organ dose table to help former patients and clinicians in charge of long-term follow-up clinics. We performed whole body dosimetric reconstruction for 2646 patients from 12 European countries treated between 1941 and 2006 (median, 1976). Most plannings were 2- or 3-dimensional. A total of 46% of patients were treated using Cobalt 60, and 41%, using a linear accelerator. The median prescribed dose was 27.2 Gy (IQ1-IQ3, 17.6-40.0 Gy). A patient-specific voxel-based anthropomorphic phantom with more than 200 anatomic structures or substructures delineated as a surrogate of each subject's anatomy was used. The radiation therapy was simulated with a treatment planning system based on available treatment information. The radiation dose received by any organ of the body was estimated by extending the treatment planning system dose calculation to the whole body, by type and localization of childhood cancer. The integral dose and normal tissue doses to most of the 23 considered organs increased between the 1950s and 1970s and decreased or plateaued thereafter. Whatever the organ considered, the type of childhood cancer explained most of the variability in organ dose. The country of treatment explained only a small part of the variability. The detailed dose estimates provide very useful information for former patients or clinicians who have only limited knowledge about radiation therapy protocols or techniques, but who know the type and site of childhood cancer, sex, age, and year of treatment. This will allow better prediction of the long-term risk of iatrogenic events and better referral to long-term follow-up clinics.